EVALUATION OF THE ELDERLY PERSON’S BIOPSYCHOSOCIAL HEALTH - Estefani Silva Nascimento, Thalita; Maria de Queiroz, Cristiane; Monique Alves Desidério, Bárbara; Michele de Araujo Pedro, Fabiana; Ellen Costa Vasconcelos, Eduarda; Barbosa Fonseca Gonçalves, Mariana; Carolina Salustino dos Santos, Maria (Health and Society, 2023)
Aging commonly presents itself as a period of vulnerability, multiple complications and, in many cases, partial or total dependence on third parties. In view of this, it is important to emphasize the responsibility of the health network to promote a positive and comfortable perspective for such users, who have been neglected and treated according to the biomedical model, ignoring the psychosocial scope of the individual and his community. Thus, it is necessary for the health system to act in terms of investing in practices aimed at this population, with psychotherapy, pharmacological therapy and multidisciplinary actions being the main means of providing a better quality of life for the elderly.